Development of intellectual and creative activity of teenagers in the study of historical and cultural monuments of England - Pirmanova, Gavkhar Nazarkulovna; Safarova, Musallam Akhmadovna; Khalilova, Zilola Farmonovna; Tashpulatova, Nargiza Samartdinovna; Normatova, Nodira Suyundikovna (Linguistics and Culture Review, 2021)
The article about the intellectual and creative activity of teenagers is especially productive if it is devoted to the knowledge of artistic values. Here, intelligence and creativity are activated. Moreover, in adolescence, there is a lively interest in art and a great need for its knowledge at the logical-cognitive and artistic-aesthetic levels. In dealing with highly artistic works (in preparing teenagers for their perception and the process itself) logical and artistic thinking develops, with the maximum activation of creative thinking and imagination, generalization, and one's attitude, as well as reproduction. However, this is not enough for teenagers: intellectual and creative potential requires its implementation in any activity of cognition. It is in this process of intellectual and creative development with the result of activities (for example, cognitive and educational) that the personality of adolescents is formed.